Code provisions evaluation for the punching shear capacity of R.C footings without reinforcement for punching shear - Amr El-said; Ahmed F. Deifalla; Saif Eldeen A.S. Yousef; Taha A. El-Sayed; Maged Tawfik; Nehal M. Ayash (Case Studies in Construction Materials, 2023)
There is no agreement on how to predict punching shear for footings among different design codes, which is inconsistent with experimentally observed capacity. Such inconsistency is due to the following issues: (1) the different definitions used by design codes for the critical section that resists the punching shear; (2) the different handling of the main parameters' influences, such as the shear slenderness, longitudinal reinforcement ratio, yielding strength of reinforcement, and compressive strength of concrete; (3) the different modelling of the subsoil underneath the footings is affecting the prediction of punching; and (4) the different modelling of the subsoil beneath the footings is affecting the prediction of punching. The current study quantified the level of safety for the various international design codes using the 195 RC column footings that had been punching shear tested and obtained from earlier investigations. Six design codes, standards, or guidelines were selected, including ACI 318–19, PrEC2, JSCE (1997), CSA and BS 8110–1 (1997), and fib Model Code (2010). The effect of the main parameters on the safety of the punching shear capacity calculated using selected methods was examined. These main parameters are concrete and reinforcement material characteristics, effective depth, column dimension, shear slenderness, and reinforcement ratio. In addition, the effect of modelling the subsoil underneath the footing is considered a parameter. It is found that all selected methods underestimate calculated punching shear capacity compared to those measured experimentally. In addition, the BS8110 is the most conservative of all selected design codes, while the second generation of the Euro code (PrEC2) is the closest to measurements and the most reliable. Moreover, the safety (Vexp/Vcalc.) of the predicted capacity using all selected methods is inversely proportional to the effective depth, the concrete compressive strength, and the column dimensions. i.e., the predicted capacity is increased with increasing these parameters, while being directly proportional to the yielding strength of reinforcement and the shear slenderness ratio, i.e., the predicted capacity is decreased with increasing these parameters. All design codes do not consider the effect of reinforcement material characteristics, even though this parameter significantly affects the results. For the flexure reinforcement ratio, the safety of the predicted punching shear capacity using ACI, CSA, and fib Model Code is directly proportional. While it is inversely proportional to the safety calculated using the PrEC2, and JSCE design codes. This is due to the fact that the PrEC2, and JSCE design codes considered the flexure reinforcement ratio while the ACI, CSA, and fib model codes neglected its effect. All selected design codes predict the punching shear capacity well if the concrete compressive strength ranges from 20 to 30 MPa, the reinforcement yielding strength is less than 500 MPa, the reinforcement ratio is less than 0.4, the effective depth ranges from 200 to 300 mm, the shear slenderness ratios are less than 2 or more than 3, and the column periphery is related to the effective depth (bo/d) between 2.0 and 6.0. Additionally, the spring simulation of the subsoil provides capacity values close to those obtained experimentally, while the sand box model, which assumes uniform soil pressure, provides the divergence values of punching capacity. The PrEC2 and fib MC2010 LOAIII design codes provided less safety than the predicted punching shear capacity for different types of sub-soil simulations.